Detecting and mapping buried buildings with Ground-Penetrating Radar at an ancient village in northwestern Argentina - Bonomo, Nestor Eduardo (2010)
We describe an archaeo-geophysical investigation performed near the Palo Blanco archaeological site, Catamarca, Argentina. A large area beyond the northern limit of the site was explored with the Ground-Penetrating Radar (GPR) method in order to detect new buildings. The exploration showed signals of mud-walls in a sector that was located relatively far from the previously known buildings. A detailed survey was performed in this sector, and the results showed that the walls belonged to a large dwelling with several rooms. The discovery of this dwelling has considerably extended the size of the site, showing that the dwellings occupied at least twice the originally assumed area. High-density GPR surveys were acquired at different parts of the discovered building in order to resolve complex structures. Interpreted maps of the building were obtained. Different characteristics of the walls were satisfactory determined, in spite of the low contrast of the dielectric constant at their interfaces and the noticeable spatial fluctuations of the signals due to wall collapses.Systematic excavations confirmed the GPR maps providing further relevant information about the characteristics of the walls and the occupational floor, as well as material for radiocarbon analyses. These analyses indicated that the discovered building was occupied until about AD 880. This fact extends 180 years the previously known period for the village, and also for the settlements in the region (formerly, AD 200 to AD 700). The performed investigations moreover confirmed different architectural characteristics assumed for Palo Blanco, related to the internal and external layouts. Interconnection between the rooms without intermediary courtyards seems to indicate a better use of the internal spaces and a more integrated spatial conception in Palo Blanco than in other villages of the region. © 2010 Elsevier Ltd.